IT support in emergency remote teaching in response to COVID-19 - Bruns, Christian; Herrmann, Tim; Böckmann-Barthel, Martin; Rothkötter, Hermann-Josef; Bernarding, Johannes; Plaumann, Markus (GMS journal for medical education, 2021)
The COVID-19 pandemic hit the German education system unexpectedly and forced its universities to shift to Emergency Remote Teaching (ERT). The Data Integration Center (DIC) of the University Hospital Magdeburg and the Institute of Biometry and Medical Informatics (IBMI) has developed a concept based on existing structures that can be quickly implemented and used by the Medical Faculty at Otto von Guericke University. This manuscript focuses on the IT support for lecturers, which allows them to concentrate on teaching their lessons, although the authors are aware that this is only a small part of the entire subject. Additionally, there is a great awareness that ERT can never replace well-structured in-person classes. The key feature of the concept uses the well-working management system for all physical rooms of the university by designing a virtual video conference room for every physical room. This allows high interactivity for lectures and seminars while applying proven teaching methods. Additionally, a collaboration software system to document all lessons learned and a technical support team have been available for the teaching staff. Courses with a hands-on approach require more personal interaction than lectures. Therefore, the issues of practical trainings have not been solved with this concept, but been tackled by using questionnaires and minimizing contacts during attestations. The concept's requirements were met by and . The concept helped the lecturers to provide high-quality teaching for students at universities. Additionally, it allows for a dynamic response to new needs and problems. The concept will be reviewed as part of a higher concept and may support lecturers in the following semesters in hybrid meetings with real and virtual attendees.